2018
DOI: 10.3389/fendo.2017.00380
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of 18F-Fluorocholine-PET/CT as Localizing Imaging Technique in Patients with Primary Hyperparathyroidism and Negative Conventional Imaging

Abstract: ObjectiveThe essential prerequisite for focused parathyroidectomy in patients with primary hyperparathyroidism (pHPT) is proper localization of all autonomic tissue. Sensitivity of conventional imaging modalities (ultrasound, 99mTc-sestamibi scintigraphy/SPECT/CT) is influenced by different factors (i.e., size/weight and position of autonomic tissue) and decreases in the presence of a multinodular goiter. Therefore, a considerable percentage of pHPT patients have negative or equivocal localization studies befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…Only Rep et al [25] reported scanning patients 3 times, at 5, 60 and 120 min after FCH injection. The FCH dosage was fixed in 16 studies, in the range of 100-230 MBq [15,[19][20][21][22][23][24][25][26][27][28][31][32][33][34]; it was adjusted to the patient's body weight in 5 (1.5-3.2 MBq/kg) and not declared in two studies [12,16,17,29,30].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only Rep et al [25] reported scanning patients 3 times, at 5, 60 and 120 min after FCH injection. The FCH dosage was fixed in 16 studies, in the range of 100-230 MBq [15,[19][20][21][22][23][24][25][26][27][28][31][32][33][34]; it was adjusted to the patient's body weight in 5 (1.5-3.2 MBq/kg) and not declared in two studies [12,16,17,29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Comparisons between FCH PET/CT and 99mTc-MIBI SPET/CT with a dual-phase and/or subtraction protocol were reported in numerous studies (Table 2; [4,[12][13][14][15][16][17][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in patients with autoimmune thyroid disease such as Hashimoto thyroiditis or Graves' disease a diffuse choline uptake in the thyroid gland can mask a possible parathyroid adenoma resulting in a false negative finding [3,[55][56][57]. However, another study documented that the presence of autoimmune thyroid disease did not compromise the use of choline PET/CT from an accurate localization of parathyroid adenoma [15,58].…”
Section: Pitfallsmentioning
confidence: 99%